2012
DOI: 10.1021/jp307038q
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Catalytic Activity Over the Iron-Modified Ce/TiO2 Catalyst for Selective Catalytic Reduction of NOx with Ammonia

Abstract: A series of iron-modified Ce/TiO 2 catalysts with different Fe/Ti molar ratios were prepared by an impregnation method and used for selective catalytic reaction (SCR) of NO x with NH 3 . The Fe−Ce/ TiO 2 catalyst with a Fe/Ti molar ratio of 0.2 had good low-temperature activity and sulfur-poisoning resistance compared with the Ce/TiO 2 catalyst. The introduction of Fe could increase the amount of Ce 3+ and chemisorbed oxygen species on the catalyst surface and thereafter generate more ionic NH 4 + and in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
99
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(104 citation statements)
references
References 36 publications
0
99
0
Order By: Relevance
“…The splitting signal we detected may have been due to the various interactions of Fe with Ti or the reduction of Fe 3+ located in different sites within the catalyst structure [22]. The third reduction peaks, which showed less intensity and appeared at 778˝C, were attributed to the reduction of Fe 2+ to Fe 0 [5,19]. After Ce doping, the H 2 -TPR profile of Fe(0.2)-Ce(0.4)-Ti catalysts showed enhanced reduction peaks.…”
Section: H 2 -Tpr Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…The splitting signal we detected may have been due to the various interactions of Fe with Ti or the reduction of Fe 3+ located in different sites within the catalyst structure [22]. The third reduction peaks, which showed less intensity and appeared at 778˝C, were attributed to the reduction of Fe 2+ to Fe 0 [5,19]. After Ce doping, the H 2 -TPR profile of Fe(0.2)-Ce(0.4)-Ti catalysts showed enhanced reduction peaks.…”
Section: H 2 -Tpr Resultsmentioning
confidence: 85%
“…This indicated that the Fe(0.2)-Ce(0.4)-Ti catalysts had more reductive species and that more chemisorbed oxygen formed on the catalyst surface after Ce doping (Table 2), which benefited the SCR reaction [19,27,28]. In addition to the enhanced reduction peak areas of the catalyst, the reduction peak of Fe 2+ to Fe 0 shifted to the lower temperature region-this reflects a strong interaction between Fe and Ce species (as further confirmed by the XPS results shown below) [4].…”
Section: H2-tpr Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Peng et al [37] improved the low-temperature activity of CeO2-WO3/TiO2 by SiO2 addition. Other transition metals such as Mo [38], Fe [39], Zr [40], and Nb [41] were also investigated as modifying agents.…”
Section: Ceria As the Main Active Component For Nh3-scr Catalystsmentioning
confidence: 99%